Mastering VMware vSphere 6.5 : leverage the power of vSphere for effective virtualization, administration, management and monitoring of data centers /: leverage the power of vSphere for effective virtualization, administration, management and monitoring of data centers. (2017) - Mauro, Andrea; Valsecchi, Paolo; Novák, Karel
No abstract available